GROWTH AND PHYSIOLOYCAL CHARACTERIZATION OF Coleus amboinicus Lour EX VITRO RESULTS OF POLYPLOID INDUCTION - Sari, Laela; Maulana, Evan; Efendi, Darda (Jurnal Agrotek Tropika, 2025)
Torbangun (Coleus amboinicus L.) is a local Indonesian medicinal plant traditionally used to promote breast milk (ASI) production. However, its propagation is limited because flowering is inhibited under unfavorable climatic conditions, and vegetative propagation through stem cuttings results in low genetic diversity. Increasing genetic variability through induced mutation and polyploidization offers a promising approach for crop improvement. To date, there has been no report on the morphological and physiological characterization of Torbangun polyploids induced by oryzalin. Therefore, this study aimed to evaluate the morphological and physiological characteristics of Torbangun clones derived from oryzalin-induced polyploidization. The plant materials consisted of six Torbangun clones (332Z, 332O, 333M, 333F, 513K, and 513W) obtained from the fifth subculture after exposure to 60 µM oryzalin for 72 hours. The experiment employed a completely randomized design (CRD) with one factor (clone) and eight replications, each represented by one plantlet per polybag. Growth parameters observed for 12 weeks included viability (%), plant height (cm), number of leaves, and number of axillary buds. Data were analyzed by ANOVA, followed by Duncan’s test for mean separation. Ploidy levels were verified using ex vitro flow cytometry. The results showed that clone 513W exhibited superior growth performance with the highest number of leaves, axillary buds, and chlorophyll and carotenoid contents. Qualitatively, induced and control plants displayed similar morphological traits, but quantitative differences were observed in leaf thickness and area. These findings provide the first comprehensive characterization of oryzalin-induced Torbangun polyploids, offering insights for future breeding and conservation efforts.